2012
DOI: 10.1021/la3008377
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Water Photolysis with Pt Metal Nanoparticles on Single Crystal TiO2 Surfaces

Abstract: Two novel deposition methods were used to synthesize Pt-TiO(2) composite photoelectrodes: a tilt-target room temperature sputtering method and aerosol-chemical vapor deposition (ACVD). Pt nanoparticles (NPs) were sequentially deposited by the tilt-target room temperature sputtering method onto the as-synthesized nanostructured columnar TiO(2) films by ACVD. By varying the sputtering time of Pt deposition, the size of deposited Pt NPs on the TiO(2) film could be precisely controlled. The as-synthesized composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…S6). This implies that plasmon absorption on the Pt/TiO 2 catalyst surface is nonsignificant [36]. The onset of bimetallic PtCu catalyst samples is, however, found to be very different.…”
Section: Ohmentioning
confidence: 92%
See 1 more Smart Citation
“…S6). This implies that plasmon absorption on the Pt/TiO 2 catalyst surface is nonsignificant [36]. The onset of bimetallic PtCu catalyst samples is, however, found to be very different.…”
Section: Ohmentioning
confidence: 92%
“…Since the metal loading is only $1 wt.% in the catalyst samples, the characteristic absorption of the TiO 2 support ($300 nm wavelength [35]) is dominant in all UV-vis spectra (Fig. 2 insets), but the shift of absorption peaks indicates plasmon characteristics of metal nanoparticles on the surface of TiO 2 [36]. The onset of UV-vis absorption for Pt (black curve) is around 305-310 nm, which is similar to the value observed for Cu/TiO 2 and TiO 2 support (300-310 nm, in Fig.…”
Section: Ohmentioning
confidence: 99%
“…Pt NPs were formed by sputtering Pt targets over TiO 2 nanorods [53] (NRs) and 1D columnar TiO 2 nanostructures [52]. Both works have shown that the deposition of Pt for 20 s has generated the most effective photoelectrodes.…”
Section: Deposition Of Her and Oer Electrocatalysts By Pvd Methodsmentioning
confidence: 99%
“…The unique properties of TiO 2 nanotube array (TNTA) with large surface area and tunable morphology has been used as the active materials for dye sensitized solar cells (11), antibacterial agents (12), hydrogen sensing (13), photocatalyst (14)(15)(16), and photoelectrochemical water photolysis (17,18). In addition, the fabrication of TNTAs using electrochemical processes have been demonstrated to be an effective photoelectrode for photoelectrochemical water splitting with markedly improved efficiency (19). The nanotube structure creates a higher surface area compared with other materials, leading to the increase in efficient absorption by scattering the path length of incident photons (20).…”
Section: Introductionmentioning
confidence: 99%
“…The transition metal modified TiO 2 nanotube arrays have been demonstrated to significantly enhance photoelectrochemical activity of hydrogen generation (19,23). Usually metals with Fermi level lower than that of TiO 2 can rapidly transfer photoexcited electrons from TiO 2 to metal particles, and, therefore, reduce the possibility of electron-hole recombination and lead to efficient charge separation (23).…”
Section: Introductionmentioning
confidence: 99%